The Phenomenon of Online Purchase Transactions Reviewed from Legal Sociology - Gunawan, Christabella (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Online buying and selling transactions are a matter of pride for everyone, both from the seller and the buyer. Amid the situation of technological development and the industrial revolution 4.0 with the onslaught of the Covid-19 pandemic, every human being who can survive and still be able to carry out his activities, as usual, is a second chance. The phenomenon during the Covid-19 pandemic regarding Community Activities Restriction Enforcement / PPKM has become a shift in cultural values in this nation. Relationships between people took a strange turn. It reduced face-to-face contact in frequency, the closure of many industries and shops, and massive restrictions in every field led to depression and mass layoffs. Various internet services appear to help every human carry out social relations online or lunch, even buying feed ingredients in a circle of disease outbreaks and each of its side effects. Every little thing can do everything online. Sociology of lunch is a new field of science that studies human behavior in society according to its generally recognized legal norms and ethics and the extent to which the law affects the general public.